Effect of controlling the number of fused rings on polymer photocatalysts for visible-light-driven hydrogen evolution. Issue 40 (29th August 2019) - Ting, Li-Yu; Jayakumar, Jayachandran; Chang, Chih-Li; Lin, Wei-Cheng; Elsayed, Mohamed Hammad; Chou, Ho-Hsiu
Abstract : The introduction of fused thiophene units into the fluorene analogues, for the first time, resulted in an improved photocatalytic performance of the polymer photocatalysts. Abstract : Searching an efficient and robust photocatalyst is important in converting solar energy into chemical energy for clean and renewable fuels. Thiophene and fluorene have been widely used in this field. However, no studies exist on understanding the effect of increasing the number of fused thiophene and fluorene rings. Herein, we demonstrated a series of polymer photocatalysts based on fused rings with fluorene (F) and indenofluorene (IF) units and fused-thiophene rings (thiophene (T), thienothiophene (2T), and dithienothiophene (3T)) in different combinations, denoted as PF n T and PIF n T, where n is the number of fused thiophene rings. We show that the increased number of fused rings on fluorene or thiophene units is important for photocatalytic performance. Particularly, without adding the noble Pt cocatalysts, our PF3T presented an excellent efficiency with a hydrogen evolution rate (HER) of 1095 µmol h −1 g −1 ( λ > 420 nm). We show that the photocatalysts are robust, that is, PF2T could be used for over 70 hours. More importantly, even when we stored PF2T in a water/methanol/TEA solution for 20 days, its photocatalytic performance remained constant. This contribution documents the first systematic study on the construction of efficient and robust polymer photocatalysts, allowing the researcher to potentially target the number of fused rings on polymers and provides an important impact in this field.